Analisis Penerapan Fuzzy Tsukamoto dalam Penentuan Kelayakan Keikutsertaan Siswa pada SNMPTN - Nur Rahmi; Lutfiah Tri Syahyaningsih; Warda Wahyuni; Surianto, Dewi Fatmarani (SISFOTENIKA, 2024)
This research implements the Fuzzy Tsukamoto method to determine the eligibility of MAN 1 Makassar City students in participating in the National Selection for State Universities (SNMPTN). The input variables used include knowledge scores, skill scores, achievements, and the number of alumni who passed the SNMPTN the previous year. Data is collected from students and school archives, then processed using fuzzy models to produce eligibility decisions. The fuzzy process includes fuzzification, inference, and defuzzification to transform input variables into concrete output values. The results showed that the Fuzzy Tsukamoto method was able to provide eligibility predictions with an accuracy rate of 76.6%. This finding confirms that the combination of knowledge, skills, achievement, and number of alumni graduated scores contribute significantly to student eligibility. This research makes an important contribution in the development of a more objective and accurate student eligibility evaluation system. In addition, the results of the study can be used as a basis for decision-making regarding the awarding of scholarships, awards, or student development programs.